Ratooning Annual Cotton (Gossypium spp.) for Perennial Utilization of Heterosis - Zhang, Xin; Zhang, Zhiyong; Zhou, Ruiyang; Wang, Qinglian; Wang, Linsong (Frontiers in Plant Science, 2020)
This paper reviews an important topic within the broader framework of the use of ratoon cotton for the development of a cost-saving and efficient method for the perennial production of hybrid cotton seeds. Cotton has a botanically indeterminate perennial growth habit and originated in the tropics. However, cotton has been domesticated as an annual crop in temperate areas worldwide. Ratoon cultivation has an important application value and is important for cotton production, breeding, and basic research. In particular, ratooned male-sterile lines have four advantages: an established root system, an indeterminate flowering habit, ratooning ability, and perennial maintenance of sterility in the absence of a matched maintainer. These advantages can help reduce the costs of producing F1 hybrid cotton seeds and can help breed high-yielding hybrid combinations because ratooning is a type of asexual reproduction that allows genotypes to remain unchanged. However, ratooning of cotton is highly complex and leads to problems, such as the accumulation of pests and diseases, decreased boll size, stand loss during severe winters, and harmful regrowth during mild winters, which need to be resolved. In summary, ratoon cotton has advantages and disadvantages for the production of hybrid cotton seeds, and future prospects of ratooning annual cotton for the perennial utilization of heterosis are promising if the mechanization of seed production can be widely applied in practice.